2021
DOI: 10.3390/ncrna7030049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the lncRNA Coded within Transglutaminase 2 Gene Impacts Several Relevant Networks in MCF-7 Breast Cancer Cells

Abstract: Long non-coding RNAs are nucleotide molecules that regulate transcription in numerous cellular processes and are related to the occurrence of many diseases, including cancer. In this regard, we recently discovered a polyadenylated long non-coding RNA (named TG2-lncRNA) encoded within the first intron of the Transglutaminase type 2 gene (TGM2), which is related to tumour proliferation in human cancer cell lines. To better characterize this new biological player, we investigated the effects of its suppression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…We analyzed the amount of several factors engaged with the transcriptional control of MDA-MB-231 cells that were cultured in the absence or presence of NC9. On the basis of evidence emerging both from the literature and from experimental research carried out in our laboratory, we have selected the following proteins: Sp1 and RXR were identified as factors of the MDA-MB-231 regulome implicated in invasiveness [ 49 ] and were associated with TG2 expression [ 50 , 51 , 52 ], while RARα, MAX, and YY1 cooperate with a non-coding RNA expressed by the TGM2 gene and are involved in the control of a panel of genes that is associated with TG2 activity in MCF-7 cells [ 53 ]. Additionally, Eukaryotic translation initiation factor 3 β (EIF3β) was recently found to be strongly associated with EMT via the Akt pathway [ 54 ], and as such, c-Myb was controlled by ZEB1 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the amount of several factors engaged with the transcriptional control of MDA-MB-231 cells that were cultured in the absence or presence of NC9. On the basis of evidence emerging both from the literature and from experimental research carried out in our laboratory, we have selected the following proteins: Sp1 and RXR were identified as factors of the MDA-MB-231 regulome implicated in invasiveness [ 49 ] and were associated with TG2 expression [ 50 , 51 , 52 ], while RARα, MAX, and YY1 cooperate with a non-coding RNA expressed by the TGM2 gene and are involved in the control of a panel of genes that is associated with TG2 activity in MCF-7 cells [ 53 ]. Additionally, Eukaryotic translation initiation factor 3 β (EIF3β) was recently found to be strongly associated with EMT via the Akt pathway [ 54 ], and as such, c-Myb was controlled by ZEB1 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the same perspective, the interaction between TG2 and non-coding RNAs in nervous system tumors could be interesting to investigate. Indeed, its potential impact on TG2-related tumorigenic processes emerged in terms of both direct and indirect regulation of TGM2 expression, affecting TG2 functions and tumor-associated processes [69][70][71]155]. On the other hand, therapeutic targeting of the cellular components that promote the disease within its microenvironment may be favorable to enhance the efficacy of standard-of-care treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The TGM2 gene not only codes for several protein isoforms, but also includes two long non-coding RNAs (lncRNAs): (i) a lncRNA (TG2-lncRNA) within the first intron of the gene, whose expression correlates with TGM2_v1 [69] and (ii) a last exons variant (LEV) containing the last three exons and the 3 ′ -UTR of the gene [70]. Although it has been suggested that lncRNAs have a role in the regulation of TGM2 transcripts in some pathological conditions, this field is thus still open to future investigations [62,[71][72][73].…”
Section: Tg2 Gene Regulationmentioning
confidence: 99%